2023
DOI: 10.1021/acs.inorgchem.3c02656
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Interfacial Engineering of Heterostructured Cobalt Phosphide Spheres/Cobalt Hydroxide Nanosheets for Overall Water Splitting

Yuan Chu,
Dan Wang,
Jibiao Wang
et al.

Abstract: Recently, transition metal phosphides (TMPs) have been widely explored for the hydrogen evolution reaction (HER) due to their advantaged activity. Nevertheless, the OER performance of TMPs in an alkaline medium is still unsatisfactory. Therefore, interfacial engineering of TMPs to enhance the OER performance is highly desirable. Herein, a Co(OH) 2 nanosheet coupled with a CoP sphere supported on nickel foam (NF) is developed by a simple two-step electrodeposition. The large surface area derived from stacked na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…OEC not only plays important roles that traps and stores photogenerated holes but also acts as catalytic active sites for the OER. In this field, many transition metal (Ni, Co, and Fe)-based phosphate complexes, (oxy) hydroxides, and layered double hydroxides have been extensively explored. For example, cobalt (oxy)­hydroxide (CoOOH) exhibits outstanding PEC OER activity in the systems like CoOOH/TiO 2 , CoOOH/P:Fe 2 O 3 , CoOOH/BiVO 4 , and CoOOH/Ta 3 N 5 . Especially, our previous studies indicated that CoOOH is inclined to promote holes transfer/trapping, thus increase the effective charge separation . However, the PEC performance of the α-Fe 2 O 3 -based photoelectrode still requires further promotion to meet the practical application.…”
Section: Introductionmentioning
confidence: 99%
“…OEC not only plays important roles that traps and stores photogenerated holes but also acts as catalytic active sites for the OER. In this field, many transition metal (Ni, Co, and Fe)-based phosphate complexes, (oxy) hydroxides, and layered double hydroxides have been extensively explored. For example, cobalt (oxy)­hydroxide (CoOOH) exhibits outstanding PEC OER activity in the systems like CoOOH/TiO 2 , CoOOH/P:Fe 2 O 3 , CoOOH/BiVO 4 , and CoOOH/Ta 3 N 5 . Especially, our previous studies indicated that CoOOH is inclined to promote holes transfer/trapping, thus increase the effective charge separation . However, the PEC performance of the α-Fe 2 O 3 -based photoelectrode still requires further promotion to meet the practical application.…”
Section: Introductionmentioning
confidence: 99%
“…4 Therefore, in order to use the electricity produced by wind and solar energy more efficiently, electrochemical storage technology is urgently needed. 5,6 At present, the most advanced electrochemical energy-storage technology can be classified into two major categories: lithium-ion batteries and supercapacitors. 7–10 Compared with lithium-ion batteries, supercapacitors exhibit many advantages such as higher power density, faster charge–discharge speed and longer cycle-life, 11–14 as illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%